State of Social Sciences in Higher Education in India. - Sohal, Sukhdev Singh (2014)
The World Social Science Report (2010) noticed ‘a confluence of crises’ and emphasised ‘demand for more and better social sciences’. Globalisation has brought a dramatic growth in economic and social inequalities both within states and internationally. There is a major disjuncture between social science and society. In order to make social science relevant, pertinent and potent, social scientists have to scrutinise their own concepts about how society works and engage in vigorous self-examination of their approaches in order to define, common tasks and set a shared agenda. It is time to rethink rather transcend the 19th compartmentalisation of knowledge, if we are to meet the challenges of the 21st Century. The social sciences have to play ‘a crucial historical role’ in the 21st Century. It is widely accepted that the social sciences can be useful in solving questions in connection with government policies. As the countries both in rich and the poor face multitude of social problems, social sciences are becoming relevant though funding is becoming a major drag in the developing and poor countries. The higher education in India has become the third largest in the world next to USA and China. Higher education provides the cutting edge. In the 21st century the wealth of nations and well-being of humankind will depend to a significant extent on ideas and knowledge.